2011
DOI: 10.1111/j.1743-6109.2010.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Stroke Among Men with Erectile Dysfunction: A Nationwide Population-Based Study

Abstract: Introduction Previous cross-sectional studies have suggested that erectile dysfunction (ED) represents an independent risk factor for future cardiovascular events. However, very few studies have attempted to examine the association between ED and subsequent stroke. Aim The aim of this study is to estimate the risk of stroke during a 5-year follow-up period after the first ambulatory care visit for the treatment of ED using na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 31 publications
2
44
2
1
Order By: Relevance
“…Thus lumen obstruction may lead to the development of ED prior to cardiac signs or stroke (22). Corroborating with this idea Lojanapiwat et al performed studies showing that patients who developed ED had endothelial dysfunction prior to the clinical symptoms.…”
Section: Stroke and Edmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus lumen obstruction may lead to the development of ED prior to cardiac signs or stroke (22). Corroborating with this idea Lojanapiwat et al performed studies showing that patients who developed ED had endothelial dysfunction prior to the clinical symptoms.…”
Section: Stroke and Edmentioning
confidence: 98%
“…More importantly, men with ED were more likely to have strokes than those without. In the others words, ED has been cited as a strong indicator of stroke, as well as a clinical marker for cerebrovascular diseases (22,(48)(49). Ponholzer et al , reported that 2,561 men with moderate to severe ED had an increased risk of stroke over 10 years (24.7% and 43.6%) (50).…”
Section: Stroke and Edmentioning
confidence: 99%
See 2 more Smart Citations
“…Die endotheliale Dysfunktion konnte als gemeinsamer pathophysiologischer Mechanismus bei kardiovaskulären Erkrankungen, sowie bei der ED ermittelt werden [6]. In mehreren Studien konnte ein klarer Zusammenhang zwischen der ED und kardiovaskulären Erkrankungen gesehen werden [7,8]. Oft ist die ED das erste klinische Zeichen , welches innerhalb 36 Monaten einen bevorstehenden Myokardinfarkt oder eine Angina pectoris voraussagt [9].…”
Section: Auch Bei Patienten Mit Vorbestehenden Vaskulären Pathologienunclassified